Pelatihan Pembuatan Kuliner Memanfaatkan Bahan Pangan Lokal Lahan Basah Di Kota Banajrmasin - Ellyn Normelani; Rusdiansyah Rusdiansyah; Salma Safitri; Mahmudah Mahmudah; Aulia Puspitasari; Rizky Nur Hakimah (Universitas Lambung Mangkurat, 2023)
Until now, the people in the locations under review have never received training in the skills of making, presenting, and packaging culinary products made from local wetlands. This community service activity aims to provide knowledge and skills for making local culinary dishes from plants in their yard. The method used is assistance and demonstrations for members of the PKK of the Purnasakti in Basirih Village, Banjarmasin City. After participating in this activity, the community have the skills to process culinary dishes made from home gardening. According to the results of the mentoring, the participants also mastered culinary creation, as seen from the demonstration results of each member's culinary creation.